2021
DOI: 10.1111/flan.12515
|View full text |Cite
|
Sign up to set email alerts
|

Multilingual, bilingual, and monolingual Arabic teachers’ development of learner self‐regulation and language awareness in the Emirates

Abstract: Multilingual learning and teaching have been receiving growing attention of late as many cities and states undergo significant demographic changes brought about by increasing levels of human migration. The onset of super‐diversity means that teachers often encounter students with very different language and cultural backgrounds in the classroom. This has created a new set of challenges and opportunities, especially concerning the teaching and learning of languages. As a result, research on language teaching an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 50 publications
(73 reference statements)
0
11
0
1
Order By: Relevance
“…This is implied in several studies where the FL teacher participants were found to implement MTPs only after reflecting on their own identity as multilingual language users (Ng, 2018;Park, 2012) and not that of their students. It is also worth emphasizing here that the multilingual initiatives launched by governments around the world, whether in Asia (Calafato, 2021a;Gao & Zheng, 2019), Europe (Calafato, 2020a;European Council, 2019), or the Middle East (Tang & Calafato, 2021), encourage students to learn multiple FLs as part of their school or university education, often two or more simultaneously. Yet, studies on the implementation of MTPs by FL teachers have seldom explored this multiplicity of languages, focusing instead purely on one language, mostly English (Calafato, 2019), with less attention paid to languages other than English (LOTEs) (Aslan, 2015;Calafato, 2020a;2021b;Brown, 2021;Haukås, 2019;Tang & Calafato, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is implied in several studies where the FL teacher participants were found to implement MTPs only after reflecting on their own identity as multilingual language users (Ng, 2018;Park, 2012) and not that of their students. It is also worth emphasizing here that the multilingual initiatives launched by governments around the world, whether in Asia (Calafato, 2021a;Gao & Zheng, 2019), Europe (Calafato, 2020a;European Council, 2019), or the Middle East (Tang & Calafato, 2021), encourage students to learn multiple FLs as part of their school or university education, often two or more simultaneously. Yet, studies on the implementation of MTPs by FL teachers have seldom explored this multiplicity of languages, focusing instead purely on one language, mostly English (Calafato, 2019), with less attention paid to languages other than English (LOTEs) (Aslan, 2015;Calafato, 2020a;2021b;Brown, 2021;Haukås, 2019;Tang & Calafato, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…It is also worth emphasizing here that the multilingual initiatives launched by governments around the world, whether in Asia (Calafato, 2021a;Gao & Zheng, 2019), Europe (Calafato, 2020a;European Council, 2019), or the Middle East (Tang & Calafato, 2021), encourage students to learn multiple FLs as part of their school or university education, often two or more simultaneously. Yet, studies on the implementation of MTPs by FL teachers have seldom explored this multiplicity of languages, focusing instead purely on one language, mostly English (Calafato, 2019), with less attention paid to languages other than English (LOTEs) (Aslan, 2015;Calafato, 2020a;2021b;Brown, 2021;Haukås, 2019;Tang & Calafato, 2021). The result is that we have an incomplete picture of the use of MTPs in FL teaching, one that does not accurately reflect the compound state of FL education in schools and universities, where students are encouraged to not only draw on their whole language repertoire but also to do so while learning multiple FLs.…”
Section: Introductionmentioning
confidence: 99%
“…For families, the commodification of multilingualism leads to language planning that prioritizes the learning of high-status languages and discourages the learning of low-status ones. These power dynamics are visible in countries like the United Arab Emirates, where parents have been found to promote the learning of English and other foreign languages (e.g., French) while according little or no importance to Arabic, despite its status as the country’s sole national language (Tang & Calafato, 2021). Lastly, the interplay between multilingualism and language planning can lead to instances of conflict, especially in TMFs, due to the presence of multiple languages and, therefore, perspectives, discourses, and behavior.…”
Section: Multilingualism and Language Planningmentioning
confidence: 99%
“…In Arabic language teaching, there are four language skills that students must have: listening, speaking, reading, and writing skills. Innovative Arabic language learning requires a suitable, interactive, and enjoyable environment to develop and improve students' skills (Aburezeq, 2020;Adam & Fitriani, 2023;Al-Muslim et al, 2020;Calafato & Tang, 2019;Dajani et al, 2014;ElHawari, 2020;Tang & Calafato, 2021). Writing skills are one of the productive skills and are considered difficult in Arabic language teaching, so teachers need a long time to teach these skills.…”
Section: Introductionmentioning
confidence: 99%